Akame ga kill! Zero. 7 - Takahiro, 1981- (Yen Press, 2018)
"Mera's carefully guided tour of the Empire has opened Akame's eyes to the suffering of its people. However, the Darburghs' loose allegiance to whoever pays them is an even less-palatable philosophy than that of the Rebel Army. Up until now, Akame has resisted Mera's advances-- professional and intimate-- but with her captor's patience running thin and her sword out of reach, Akame will have to rely on a whole new set of skills if she wants to survive!" -- Page [4] of cover.